Some revisions of virtue ethics - Hoyos Valdés, Diana (Estudios de Filosofía, 2011)
There are at least two reactions to the reemergence of virtue ethics: first, there are those who believe that such ethics is unnecessary because the modern moral theories include –or can include— the virtues. Secondly, there are those who think that the ethics of virtue is a more wide and complete moral theory than the modern ones. In this paper, the reemergence of virtue ethics is presented and the two reactions mentioned are examined. Finally, it is asked for the reason to prefer the ethics of virtue.